Vincent van Gogh and the colors of the wind - Lossani, Chiara; Gogh, Vincent van, 1853-1890.; Monaco, Octavia (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2011)
An illustrated look at the life of Vincent van Gogh, discussing his inspirations and struggles, focusing on his close relationship with his brother Theo, and showcasing fourteen of his paintings.
Booklist
Kirkus Review
Booklist, January 2011
Kirkus Review, December 2010
5.2
3-6
Keywords: Gogh, Vincent van, -- 1853-1890 -- Juvenile literature; Gogh, Vincent van, -- 1853-1890.; Gogh, Vincent van, -- 1853-1890.; Painters -- Netherlands -- Biography -- Juvenile literature; Painters; Painters -- Biography; Picture books for children